Public Mental Health – Using the Mental Health Gap Action Program to Put all Hands to the Pumps - Uwakwe, Richard; Otakpor, Alex (Frontiers in Public Health, 2014)
Mental ill health constitutes a huge portion of the GBD but the majority of people with mental health problems do not receive any treatment, a scenario much worse in developing countries where mental health personnel are in gross short supply. The mhGAP was launched to address this gap, especially by training non-mental health professionals to deliver effective services for selected priority mental health problems. Especially in developing countries, people with mental health problems consult traditional healers either as a first step in the pathway to biomedical mental health care or as the sole mental health service providers. Bridging the gap between mental health needs and available services in developing countries must incorporate traditional healers, who are ubiquitously available, easily accessible and acceptable to the natives. Although there are barriers in forging collaborations between traditional and biomedical mental health care providers, with mutual respect, understanding and adapted training using the mhGAP guide it should be possible to get some traditional healers to understand the core principles of some priority mental health problems identification, treatment and referral.